2020
DOI: 10.1016/j.str.2020.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Peptidoglycan Synthase Activator LpoP in Pseudomonas aeruginosa

Abstract: Highlights d Structural organization of LpoP has been resolved d Pa PBP1B is directly stimulated by LpoP but not by Pa CpoB

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
3
11
0
Order By: Relevance
“…The addition of LpoP Pa (sol) resulted in an increase in the final FRET by ~2.2-fold in the membrane and ~2.1-fold in detergents ( Figure 3G , Figure 3—figure supplement 8A ), and accelerated initial slopes by ~4.2-fold in the membrane and ~11.5-fold in detergents ( Figure 3H , Figure 3—figure supplement 8B ); lipid II consumption was increased under both conditions ( Figure 3G , right, Figure 3—figure supplement 8C ). Overall, these results indicate that LpoP Pa (sol) stimulates both GTase and TPase activities in agreement with a recent report ( Caveney et al, 2020 ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The addition of LpoP Pa (sol) resulted in an increase in the final FRET by ~2.2-fold in the membrane and ~2.1-fold in detergents ( Figure 3G , Figure 3—figure supplement 8A ), and accelerated initial slopes by ~4.2-fold in the membrane and ~11.5-fold in detergents ( Figure 3H , Figure 3—figure supplement 8B ); lipid II consumption was increased under both conditions ( Figure 3G , right, Figure 3—figure supplement 8C ). Overall, these results indicate that LpoP Pa (sol) stimulates both GTase and TPase activities in agreement with a recent report ( Caveney et al, 2020 ).…”
Section: Resultssupporting
confidence: 93%
“…Our assay revealed the effect of Lpo activators on PBP1B analogues from three bacteria. P. aeruginosa uses LpoP to stimulate its PBP1B ( Greene et al, 2018 ; Caveney et al, 2020 ). Here, we identified an LpoP homologue in A. baumannii and showed that it stimulated its cognate PBP1B.…”
Section: Discussionmentioning
confidence: 99%
“…Our experiments revealed differences in the activities and effect of activators between both PBP1B-homolgoues which we discuss in the following paragraphs. these results indicate that LpoP Pa (sol) stimulates both GTase and TPase activities in agreement with a recent report (Caveney et al, 2020).…”
Section: Activities Of Other Membrane-bound Class a Pbpssupporting
confidence: 94%
“…The following proteins were purified following published protocols: PBP1B Ec (Bertsche et al, 2006), LpoB(sol) (Egan et al, 2014), PBP1B Pa (Caveney et al, 2020), LpoP Pa (sol) (Caveney et al, 2020). All chromatographic steps were performed using an AKTA PrimePlus system (GE Healthcare).…”
Section: Purification and Labelling Of Proteinsmentioning
confidence: 99%
“…LpoB conservation is even more limited: LpoB homologs are found only in a subset of gammaproteobacteria (12,112). Interestingly, unique class A PBP cofactors have evolved independently in some Gram-negative and actinobacteria (112,113), some of which also possess intrinsically disordered linkers (114). Mechanisms of cell wall quality control are equally, if not more, mysterious in Gram-positive bacteria.…”
Section: Responses To Acute Cell Wall Damagementioning
confidence: 99%